2017
DOI: 10.3389/fphar.2017.00189
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating Quality of Decision-Making Processes in Medicines' Development, Regulatory Review, and Health Technology Assessment: A Systematic Review of the Literature

Abstract: Introduction: Although pharmaceutical companies, regulatory authorities, and health technology assessment (HTA) agencies have been increasingly using decision-making frameworks, it is not certain whether these enable better quality decision making. This could be addressed by formally evaluating the quality of decision-making process within those organizations. The aim of this literature review was to identify current techniques (tools, questionnaires, surveys, and studies) for measuring the quality of the deci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 31 publications
(80 reference statements)
0
23
0
1
Order By: Relevance
“…6 A recent review of the literature identified general paucity of research in this area, particularly regarding the development and systematic application of techniques for evaluating quality decision-making, such as through the studies undertaken as part of this research. 9 Indeed this is the first assessment to evaluate quality of decision-making within the different organisations involved in the development, review and reimbursement of medicines.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…6 A recent review of the literature identified general paucity of research in this area, particularly regarding the development and systematic application of techniques for evaluating quality decision-making, such as through the studies undertaken as part of this research. 9 Indeed this is the first assessment to evaluate quality of decision-making within the different organisations involved in the development, review and reimbursement of medicines.…”
Section: Discussionmentioning
confidence: 99%
“…A systematic review of the literature demonstrated QoDoS to be the most promising available technique for such assessments. 9 Moreover, a pilot study with participants from pharmaceutical companies and regulatory authorities demonstrated the initial practicality of the QoDoS in assessing the strengths and weaknesses as well as similarities and differences in decision-making practices amongst individuals as well as their perception of their organisation. 10 Furthermore, a recent study demonstrated the reliability and relevance of QoDoS in the decision-making of pharmaceutical companies, regulatory authorities and HTA agencies.…”
Section: Key Messagesmentioning
confidence: 99%
“…The practicality of the tool in a regulatory authority and pharmaceutical company setting was confirmed through a study with 76 participants (50% from regulatory authorities and 50% from pharmaceutical companies) (Bujar et al, 2016). The findings of this pilot study as well as the results of a recent systematic review (Bujar et al, 2017) have demonstrated that the QoDoS is considered to be the most promising instrument for evaluating quality of the decision-making process during medicines development and review, identifying strengths and weaknesses and raising awareness of the issues in quality decision making across individuals and within organisations. The challenge is how to ensure that the QoDoS, in addition to the above described attributes, produces reliable, and relevant results.…”
Section: Introductionmentioning
confidence: 88%
“…The CIRS-BRAT tool allows users to generate tabular and graphical displays to assist in the interpretation of benefit and risk findings. 33 The purpose of the tool is to enable users to generate value trees, key benefit-risk summary tables, and forest plots. 33 The ICH guideline M4E entitled "Common technical document for the registration of pharmaceuticals for human use -Efficacy" was revised in order to standardize the content and presentation of benefit-risk information in regulatory submissions.…”
Section: Benefit-risk Assessmentmentioning
confidence: 99%
“…33 The purpose of the tool is to enable users to generate value trees, key benefit-risk summary tables, and forest plots. 33 The ICH guideline M4E entitled "Common technical document for the registration of pharmaceuticals for human use -Efficacy" was revised in order to standardize the content and presentation of benefit-risk information in regulatory submissions. The Revised ICH M4E(R2) guideline specifies a structure for the Common Technical Document (CTD) in Section 2.5.6, Benefits and Risk Conclusions.…”
Section: Benefit-risk Assessmentmentioning
confidence: 99%